Step-by-step explanation: do fast
when you will upload the picture do fast
You have (-3 +i)/(7 + i) so you need to remove the i from the numerator, so you have to multiply by 7-i and you get
(-22 + 4i)/50 which can be simplified to
(-11 + 2i)/25
Answer:
Step-by-step explanation:
66666666666
Well
if it is marked 1/3 off, then you're actually paying 2/3 of it.
2/3 of 123. " of " means multiply
2/3 * 123 = 246/3 = 82 So it now costs $ 82
Answer:
Step-by-step explanation:
a = 2, b = 1, c = -3
We need to factor this by finding the product of a and c, then from there find which factors of a * c will either add or subtract to give us b.
a * c = 6 and the factors of 6 and 1 and 6, 2 and 3. Well, 6 - 1 doesn't equal 1 and neither does 6 + 1. So our factors are 3 and 2. In order to combine those to get a 1 (our b), we will subtract 2 from 3 since 3 - 2 = 1. That means that 3 is positive and 2 is negative. Filling in the formula with 3 and 2 in place of 1 looks like this (always remember to put the absolute value of the largest number first):
![2x^2+3x-2x-3=0](https://tex.z-dn.net/?f=2x%5E2%2B3x-2x-3%3D0)
Group the first 2 terms together and the second 2 term together in order to factor:
and factor out what's common in each set of parenthesis.
![x(2x+3)-1(2x+3)=0](https://tex.z-dn.net/?f=x%282x%2B3%29-1%282x%2B3%29%3D0)
Notice that when we factor out a -1 from the second set of parenthesis, we can distribute it back in to get the equation we started with. We know that factoring by grouping "works" if what is inside both sets of parenthesis is exactly the same. Ours are identical: (2x + 3). That is common now, and can be factored out:
![(2x+3)(x-1)=0](https://tex.z-dn.net/?f=%282x%2B3%29%28x-1%29%3D0)
That matches your first choice